PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH, PENYAJIAN LAPORAN KEUANGAN, AKSESIBILITAS LAPORAN KEUANGAN DAN AKTIVITAS PENGENDALIAN TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (Studi Empiris Pada SKPD Kabupaten Kampar Tahun 2017) - Awalia, Rahmi; Agusti, Restu; Wiguna, Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted on Kampar district government. This research is included in quantitative research. The type of data used in this study is primary data is data derived from the next source in data collection techniques, sampling is done by Purposive Sampling method of sampling technique with certain considerations (Sugiyono, 2012: 116 with respondents as many as 116 employees who work in SKPD Kabupaten Kampar data was analyzed using multiple linear regression analysis with SPSS Version 21. This study aims to determine the effect of Regional Financial Accounting System, Presentation of Regional Financial Statements, Accessibility of Financial Statements and Control Activities to Accountability of Regional Financial Management. The main issues that will be explained by the researcher are as follows: To see how big influence and signifikan between dependent variable with independent variable. The results of this study indicate that the Regional Financial Accounting System has an effect on the Accountability of Regional Financial Management, Presentation of Regional Financial Report has an effect on to Accountability of Regional Financial Management, Accessibility of Financial Statement has an effect on to Accountability of Regional Financial Management and Control Activity Influence to Accountability of Regional Financial Management with significance value 0,008 , 0.003, 0.012 dean 0.000 Contribution of variable variable of Regional Financial Accounting System, Presentation of Regional Financial Report, Accessibility of Financial Statement and Control Activity can explain variable of Accountability of Regional Financial Management at Regency Government of Kampar equal to 78,6%. While the remaining 21.4% is influenced by the variables not observed in this research model.Keywords: Accountability, Regional Financial Accounting System, Financial Statement, Accessibility, and Control Activities